Discussion on Fashion Color Forecasting Researches for Textile and Fashion Industries (Journal of Fiber Bioengineering and Informatics, 2018)
Overview of researches on fashion color forecasting. Concern the important contributions and achievements on fashion color forecasting researches. Divide the current researches into two main types: systematic analysis system and historical color data analysis in terms of the objectivities. Propose the common methodologies applied in the researches: personal color preference investigation (systematic analysis), rough set, grey theory, statistical analysis etc. Discuss the deficiencies, including data collection and prediction model problems that existed in the current forecasting researches.